Application of humanistic care with characteristics of Traditional Chinese Medicine in conservative treatment of cervical spondylosis (中医特色人文关怀在颈椎病患者保守治疗中的应用) - YANG Jinrui (杨金瑞); ZHANG Xuejian (张雪键); CUI Yangfang (崔杨芳) (Association of Integrative Nursing, 2023)
Objective To explore the effect of humanistic care with characteristics of Traditional Chinese Medicine(TCM) in conservative treatment of cervical spondylosis. Methods A total of 42 patients with cervical spondylosis treated conservatively were were randomly divided into the study group and the control group, with 21 cases in each group. The control group was given routine nursing interventions during hospital stay, and study group received humanistic care with characteristics of TCM on the basis of the routine care. The scores of Northwick Park Neck Pain Questionnaire(NPQ), Pittsburgh sleep quality index (PSQI), Self-rating Anxiety Scale(SAS) and Self-rating Depression Scale (SDS) , length of hospital stay and patients satisfaction with nursing service of two groups were compared. Results Scores of NPQ and PSQI in the study group were lower than those in the control group after nursing interventions(P＜0. 01). Scores of SAS and SDS in the study group were lower than those in the control group after nursing interventions(P＜0. 01). The length of stay in the study group was shorter than that in the control group (P＜0. 01). Score of satisfaction assessment in the study group was higher than that in the control group(P＜0. 01). Conclusion Humanistic care with TCM nursing interventions is effective to relieve the clinical symptoms of patients receiving conservative treatment of cervical spondylosis, and it may help relieve negative mood, improve the sleep quality, shorten the length of stay and improve the satisfaction degree of patients. (目的 探讨中医特色人文关怀在颈椎病患者保守治疗中的护理效果。方法 选取医院收治的42例颈椎病保守治疗的患者为研究对象, 随机分为研究组和对照组, 各21例。对照组接受常规护理干预模式, 研究组在对照组的基础上运用中医特色人文关怀护理模式进行干预。采用Northwick Park 颈痛量表(NPQ)评估颈痛程度, 采用匹兹堡睡眠质量指数(PSQI)评估睡眠质量, 采用焦虑自评量表(SAS)和抑郁自评量表(SDS)评估患者负性情绪, 记录两组住院时间, 评价护理满意度。结果 护理干预后, 研究组NPQ量表评分和PSQI量表评分均低于对照组, 差异有统计学意义(P＜0. 01); 研究组SAS和SDS量表评分低于对照组, 差异有统计学意义(P＜0. 01); 研究组总住院时长较对照组缩短(P＜0. 01); 研究组患者满意度评分高于对照组(P＜0. 01)。结论 中医特色人文关怀护理干预可有效缓解颈椎病患者保守治疗期间的临床症状, 有利于减轻其疼痛程度, 提高睡眠质量, 缓解负面情绪, 缩短其住院时长, 提升住院患者对护理的满意度。)